REST, RESTORATION, AND RENEWAL IN LEVITICUS 25: A THEOLOGICAL VISION FOR AFRICA’S SUSTAINABLE FUTURE - Agoha, Emmanuel Chijioke; Kokey, Grace Chinedum (African Journal of Social and Behavioural Sciences, 2025)
Africa’s deepening crises of socio-economic inequality, ecological degradation, and moral disintegration reveal the insufficiency of secular sustainability models that lack theological grounding. Yet scholarship has not adequately retrieved the Jubilee legislation of Leviticus 25 as a normative framework for African transformation beyond ritual or historical interpretation. This study, therefore, examines the theological logic of rest, restoration, and renewal in Leviticus 25 and its implications for Africa’s sustainable future. The paper is guided by the questions to show how the Jubilee legislation in Leviticus 25 relates to the motifs of rest שבת (shabbath), restoration ) שוב shuv), and renewal חָדַשׁ (chadash) relate to Africa. Methodologically, it employs a qualitative and interpretive approach that integrates exegetical analysis of the Hebrew text with contextual theological reflection. The study is theoretically grounded in covenantal-restorative justice theology, which emphasizes God’s ordering of communal life, ethical land stewardship, and human dignity within covenant relationship. Findings indicate that the Jubilee offers a comprehensive theological and ethical model that integrates Sabbath spirituality, distributive justice, ecological renewal, and communal identity. The paper concludes that a Jubilee-informed theological vision addresses a critical gap in African sustainability discourse by offering a holistic paradigm of rest, restorative justice, and ecological renewal grounded in covenant theology.